Pengaruh Motivasi Dan Pengembangan Karir Terhadap Kinerja Melalui Kepuasan Kerja Karyawan AJB Bumiputera 1912 Wilayah Semarang Metro - Anita Permata Sari; Saryadi Saryadi; Widiartanto Widiartanto (Universitas Diponegoro, 2015)
Based on Gross Domestic Product in the year of 2007 insurance sector only show 1,88% compared with the other banking sector which reach 2,67% in the same year. That explanation indicates that public’s attention regarding to insurance issue is still limited. This condition demands company to adapt in global competition through human resources management. The management of human resources which are being referred to is factors that influnce job performance of the employee as a part of company asset. It refers to motivation, career development, and job satisfication. The main problem in this research is about target that is never reached in 2010-2013 with provision of the minimum point is 100%. The objective in this research is to find out the influence of motivation and career development on job performance through job satisfication at AJB Bumiputera 1912 Semarang Metro District.This type of research is explanatory research. The population on this research are employees of AJB Bumiputera 1912 Semarang Metro District and the number of sample are 97 respondents. The technique of sampling used is proportionate random sampling. Analysis method used are correlation coefficient test, determination coefficient test, simple regression analysis, multiple regression analysis, t test, F test and path analysis with SPSS Program version 16.The result from path analysis is motivation and career development have bigger effect to job performance, if it’s through to job satification. It shows that if the employees’ motivation is getting higher and career development which is also getting better along with job satisfication that is also high, it will increase the job performance from the employees. Suggestion for AJB Bumiputera 1912 Semarang Metro district are related to socialization about reward system at the company and evaluation about standard operational procedure that should be suitable with the current situation for increasing the independence and as a motivation for the employees in order to do optimal work and give satisfied result.